Nursing homes and mortality in Europe: Uncertain causality. (7th October 2022) - Flawinne, Xavier; Lefebvre, Mathieu; Perelman, Sergio; Pestieau, Pierre; Schoenmaeckers, Jérôme
Abstract: The current health crisis has particularly affected the elderly population. Nursing homes have unfortunately experienced a relatively large number of deaths. On the basis of this observation and working with European data (from SHARE), we want to check whether nursing homes were lending themselves to excess mortality even before the pandemic. Controlling for a number of important characteristics of the elderly population in and outside nursing homes, we conjecture that the difference in mortality between those two samples is to be attributed to the way nursing homes are designed and organized. Using matching methods, we observe excess mortality in Sweden, Belgium, Germany, Switzerland, Czech Republic and Estonia but not in the Netherlands, Denmark, Austria, France, Luxembourg, Italy and Spain. This raises the question of the organization and management of these nursing homes, but also of their design and financing.